La physiologie des Lumières - Duchesneau, François (Man and Nature / L'homme et la nature)

(untitled) (Canadian Society for Eighteenth-Century Studies / Société canadienne d'étude du dix-huitième siècle, 1984)
Using a method which emphasizes the importance of the explanatory systems of the past for the history of science, this article studies eighteenth-century theories of irritability and muscular contraction. The main focus is on Albrecht von Heller and the way his theories are analogous to Newtonian "principles."